2020
DOI: 10.1016/j.compgeo.2019.05.007
|View full text |Cite
|
Sign up to set email alerts
|

Formulation and implementation of a practical multi-surface soil plasticity model

Abstract: This paper presents a new constitutive model for clay, for undrained monotonic and cyclic loading, that has been developed specifically for geotechnical design applications. The model employs a parallel Iwan approach, consisting of multiple elastic-perfectly-plastic micro models. Degradation of stiffness and strength during cyclic loading is incorporated using an empirical cyclic overlay method. The theoretical framework and calibration processes for the model are presented. An implementation of the model in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 48 publications
(73 reference statements)
0
7
0
Order By: Relevance
“…1) κ* 0.5 Variation of hardening slope h p 1 for cyclic modelling of piles and conductors (e.g. Whyte et al 2020), and the PICSI model provides an overlay that captures soil softening and consolidation. This opens up the possibility of efficiently modelling the full 'whole life' history of changing soil support.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1) κ* 0.5 Variation of hardening slope h p 1 for cyclic modelling of piles and conductors (e.g. Whyte et al 2020), and the PICSI model provides an overlay that captures soil softening and consolidation. This opens up the possibility of efficiently modelling the full 'whole life' history of changing soil support.…”
Section: Discussionmentioning
confidence: 99%
“…These stiffness values are the secant peak-to-peak stiffness within a cycle, K = δF h /y pp where δF h is the difference between the peak values of horizontal force at each cyclic limit and y pp is the pile displacement between these peak values of This formulation does not recognise cyclic loading as being more damaging than monotonic loading to the same accumulated deformation, which is a limitation that is tolerated in other practical models for soil softening (e.g. Whyte et al 2020). More complex alternatives could be used in place of Eq.…”
Section: Generation Of Damagementioning
confidence: 99%
“…The non-linear springs may also be supplemented by non-linear damping elements, which can be depth-dependent. The P-Y curve method does not take into account the hysteretic behaviour of soil as is suggested in some relevant literature Whyte et al (2020), but does capture the strong strain-softening non-linear behaviour observed in most soils. The non-linear springs are usually defined using empirical relations dependent upon various properties of the specific soil type considered or by calibration with FE models.…”
Section: Soil Structure Interaction In Wind Turbinesmentioning
confidence: 99%
“…However, as the current study provides a guideline to the researcher for transferring the physical tests to the numerical simulation, the researcher may choose a more appropriate soil model to represent their dynamic problem. Three examples of advanced cyclic soil models, i.e., bounding surface plasticity model [57]; [58], multi-surface plasticity model [59]; [60]could be an excellent solution depending on the nature and complexity of the problem. [17], to validate the numerical approach.…”
Section: Cam-clay Modelmentioning
confidence: 99%